VSG mRNA levels are regulated by the production of functional VSG protein - Maudlin, Isabella E. (Mol Biochem Parasitol, 2021)
The bloodstream form of Trypanosoma brucei persists in mammalian hosts through a population survival strategy depending on antigenic variation of a cell surface coat composed of the variant surface glycoprotein (VSG). The integrity of the VSG coat is essential and blocking its synthesis results in a cell division cycle arrest just prior to cytokinesis. This observation indicates that VSG levels are monitored and that the cell has mechanisms to respond to a disruption of synthesis. Here, the regulation of VSG mRNA levels has been investigated by first measuring VSG mRNA copy number, and second using ectopic expression of VSG transgenes containing premature termination codons. The findings are that (i) VSG mRNA copy number varies with the identity of the VSG and (ii) a pathway detects synthesis of non-functional VSG protein and results in an increase in VSG mRNA levels.